Galen's Treatise Περὶ Ἀλυπίας (De indolentia) in Context A Tale of Resilience - Petit, Caroline (Studies in Ancient Medicine, 2019)
This volume offers a multi-disciplinary approach to the "new" Galen text De indolentia, discovered in 2005. It addresses Galen's literary production, his medical and philosophical contribution, the Antonine plague, the reign of Commodus, and finally the reception of the text. Readership: All interested in Galen, ancient Greek philosophy, Roman history, the history of medicine, and the history of literature.